An exploratory study on Mom and Pop shops : surviving the trade. - Chua, Yew Teck. (2012)
In a challenging business landscape that is constantly evolving, small businesses have seen little incentive to continue or survive their trade effectively, a situation that resounds globally today. Due to the volatile nature of the industry, small businesses also tend to have differing degrees of success. This can be attributed to the fact that most business owners often “do not have a clue of how to run a business and have no underlying appreciation of business fundamentals drivers behind changes” (Barron et al, 2007).